Studi Deskriptif Efektivitas Media Pembelajaran Magic Board pada Materi FPB dan KPK di Kuttab Al Kahfi Indonesia - Rahma Siratu Rahmi; Salati Asmahasanah; M. Kholil Nawawi (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to determine effectivenees of magic board on FPB and KPK learning in the Kuttab Qanuni class one, where the class is the second level in Kuttab Al Kahfi Indonesia, Kuttab Qanuni one is equivalent to the fourth grade in elementary school. Kuttab Al Kahfi Indonesia has the advantage of adab, where in Kuttab Al Kahfi Indonesia instills in students adab before science. Because adab is more important than knowledge, civilized people must be knowledgeable, but people who are knowledgeable are not necessarily civilizet. This research method uses descriptive qualitative method. This research was conducted in the Kuttab Qanuni class one Kuttab Al Kahfi Indonesia, which consisted of eight people. The method of colleting data of obtain the results of this study is by conductng observations, documentation, and interviews. The results of motivate students by using learning media, increasing students’ curiosity by using learning media, and increasing student communication with teachers in creating a learning atmosphere. Keywords : Learnig Media, Learning Effectiveness, FPB KPK, Magic Board.